Impact of a brief intervention programs in clinical practice: Barriers and adaptations (2018)
Introduction: The present study analyzes the main barriers and adaptations to brief interventions that focus on addictive behavior treatments carried out in clinical settings by 756 health professionals during their adoption process in 350 Primary Attention Units in Mexico. Method: A descriptive cross-sectional study was conducted and consisted in the application of an instrument that explored diverse aspects, such as knowledge about evidence based brief intervention (BI) programs, barriers during the execution, and adaptations of the BI. Results: the main barriers were related to the implementation of sessions and the user’s characteristics such as educational level. As a consequence, the main adaptations were related to the increase in the number of sessions, modifying their length and changing the sequence as well as the proposed material in the manuals. Conclusions: We discuss the possibility of systematizing the adaptations made by health professionals in order to evaluate their effectiveness